Shear Wave Elastography in the Differentiation of Nonfibrotic Versus Fibrotic Liver Disease in Children: A Prospective Study With Histological Correlation. Issue 1 (10th February 2022) - Hebelka, Hanna; de Lange, Charlotte; Boström, Håkan; Ekvall, Nils; Lagerstrand, Kerstin
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: To evaluate the diagnostic accuracy of ultrasound shear wave elastography (SWE) prospectively and to determine cutoff value for nonfibrotic liver tissue in children with suspected or established liver disease. Methods: In 90 consecutive pediatric patients, standardized 2D-SWE was performed during general anesthesia and free breathing. Liver stiffness was estimated with SWE followed by a percutaneous biopsy from the corresponding area. SWE values were compared with histology with fibrosis scored according to Batts & Ludwig classification (grade 0–4 = F0–F4) and to hepatic biomarkers. Results: Four patients with SWE interquartile range (IQR)/median ≥ 30% kPa were excluded. The remaining 86 children (59% males) had a mean age = 10.2 years (0.1–18). The distribution of individuals with median (min;max) SWE values (kPa) within each fibrosis grade were; F0[n = 10; 5.0(3.4;6.3)], F1[n = 24; 5.0(3.6;8.7)], F2[n = 32; 5.8(3.5;13.4)], F3[n = 12, 7.5(4.0;14.4)], and F4[n = 8; 12.5(6.6;21.0)]. There was a significant difference between fibrosis grades (0.03 > P < 0.002) except between F0 and F1 respectively between F1 and F2. The AuROC differentiating F0-1 from F2-4 was 0.77(95% CI: 0.67-0.87). A cutoff SWE value of ≤4.5 kPa yielded 90% sensitivity and 68% specificity to rule out significant fibrosis (F2–F4). Out of the 18 children (21%) with SWE value ≤4.5 kPa, 12 had grade F0-1 and 6 had F2, although including some confounders for increased SWE measurements as steatosis/hepatitis/cholestasis. Conclusions: 2D-SWE ultrasound can reliably distinguish no/mild (F0/F1) from moderate/severe (F2–F4) fibrosis in children with suspected/established liver disease with good sensitivity and acceptable specificity. Our results show that in pediatric patients, when the indication for biopsy is to rule out significant fibrosis, SWE can be considered an alternative.